2020
DOI: 10.1186/s12931-020-01566-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-related biomarkers in pulmonary hypertension patients on oral therapies

Abstract: Background Multiple classes of oral therapy are available for the treatment of pulmonary arterial hypertension (PAH), but there is little to guide clinicians in choosing a specific regimen or therapeutic class. We aimed to investigate whether treatment-relevant blood biomarkers can predict therapy response in prevalent PAH patients. Methods This prospective cohort study longitudinally assessed biomarkers along the endothelin-1 (ET-1) and nitric oxide (cGMP, ADMA, SDMA, nitrite, and S-nitrosohemoglobin) pathwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, the activated upstream PI3K could trigger AKT, activating the phosphorylation sites of eNOS Ser1177 and Thr495 to promote NO synthesis [17][18][19]. Subsequently, the soluble guanylate cyclase (sGC) in the vascular smooth muscle cells could be activated, converting guanosine triphosphate (GTP) into cyclic guanosine monophosphate (cGMP), thereby activating cGMP-dependent protein kinases G (PKG), leading to vasodilation and limiting pulmonary hypertension [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the activated upstream PI3K could trigger AKT, activating the phosphorylation sites of eNOS Ser1177 and Thr495 to promote NO synthesis [17][18][19]. Subsequently, the soluble guanylate cyclase (sGC) in the vascular smooth muscle cells could be activated, converting guanosine triphosphate (GTP) into cyclic guanosine monophosphate (cGMP), thereby activating cGMP-dependent protein kinases G (PKG), leading to vasodilation and limiting pulmonary hypertension [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a novel and reliable biomarker that is easy to measure is desired for PH. Previous studies have reported that plasma endothelin-1 and cyclic guanosine monophosphate (cGMP)/NT-proBNP ratio were related to 6MWD 14 , and increased serum interleukin (IL)-6/ IL-8/IL-10/IL-12 predicted worse survival 15 in patients with PAH. In the current study, although cGMP and cytokines were not evaluated, serum ANGP-2 was identified as a useful biomarker for the diagnosis of PH.…”
Section: Discussionmentioning
confidence: 99%